Coffee consumption modulates inflammatory processes in an individual fashion. Issue 12 (30th August 2016) - Muqaku, Besnik; Tahir, Ammar; Klepeisz, Philip; Bileck, Andrea; Kreutz, Dominique; Mayer, Rupert L.; Meier, Samuel M.; Gerner, Marlene; Schmetterer, Klaus; Gerner, Christopher
Abstract : Following an ex vivo approach, blood was sampled before and one hour after coffee consumption. Afterwards, peripheral blood mononuclear cells were isolated and in vitro inflammatory activated. From the cell supernatant lipids as well as proteins were extracted and processed for subsequent analysis. A mass spectrometric multiple reaction monitoring analysis was applied and the results of coffee effects on modulation of inflammatory response are represented in the heat map. Abstract : Scope: Anti‐inflammatory effects of coffee consumption have been reported to be caused by caffeine and adenosine receptor signaling. However, contradictory effects have been observed. Many kinds of chronic diseases are linked to inflammation; therefore a profound understanding of potential effects of coffee consumption is desirable. Methods and results: We performed ex vivo experiments with eight individuals investigating peripheral blood mononuclear cells isolated from venous blood before and after coffee consumption, as well as in vitro experiments applying caffeine on isolated cells. After in vitro inflammatory stimulation of the cells, released cytokines, chemokines, and eicosanoids were determined and quantified using targeted mass spectrometric methods. Remarkably, the release of inflammation mediators IL6, IL8, GROA, CXCL2, CXCL5 as well as PGA2, PGD2, prostaglandin E2 (PGE2), LTC4, LTE4, and 15S‐HETE was significantly affected after coffee consumption. While in several individuals coffee consumption or caffeine treatment caused significant downregulation of most inflammation mediators, in other healthy individuals exactly the opposite effects were observed. Conclusion: Ruling out age, sex, coffee consumption habits, the metabolic kinetics of caffeine in blood and the individual amount of regulatory T cells or CD39 expression as predictive parameters, we demonstrated here that coffee consumption may have significant pro‐ or anti‐inflammatory effects in an individual fashion.